HOW PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, SECURITY AND LIFESTYLE AFFECT MSMEs’ ADOPTION OF QRIS? - Aiza Nur Rahmah; Ilham Ilham; Nilam Anggar Sari (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
PURPOSE - This research explores the impact of perceived usefulness, perceived ease of use, security, and lifestyle on the adoption of the Quick Response Code Indonesian Standard (QRIS) by micro, small, and medium enterprises (MSMEs) in Tenggarong City.METHODOLOGY - Employing an associative approach, the study analyzes quantitative data from 100 respondents using SPSS version 26 for Windows. The methodology incorporates multiple linear regression analysis, classical hypothesis testing, and coefficient of determination.FINDING - The findings reveal that perceived usefulness, perceived ease of use, security, and lifestyle significantly and positively affect the decision to adopt QRIS, both separately and together. Notably, perceived usefulness is identified as the most significant factor, indicating that users primarily evaluate the advantages of QRIS before reaching a decision. Additionally, this study reinforces the Technology Acceptance Model (TAM) in the context of Indonesian MSMEs, highlighting that perceived usefulness and ease of use are crucial factors in technology adoption, alongside other considerations like security and lifestyle.